Impactos da urbanização em corpos hídricos na cidade de Apucarana-PR - Correia, Camila Nagy (2023)
The relationship between human and natural activities is crucial to understanding environmental transformations. Monitoring studies that analyze land use over time are essential to understand changes under human influence in urban areas. With a growing population and a complex network of watercourses in Apucarana, the need to assess and mitigate urban pressure on these water bodies becomes evident. The objective of this work was to analyze the transformation of land use and occupation in Apucarana, considering the years 1985, 2000 and 2021, with the aim of evaluating the impact generated on the water bodies present in the urban area of the city. With this, we sought to obtain a more comprehensive understanding of changes in land use and occupation in Apucarana, identifying the impacts of these transformations on water bodies and providing subsidies for urban planning and environmental management in the city. To this end, maps of land coverage and use were prepared for both the municipality and the urban area, considering the respective time periods, to analyze the main transformations that occurred. Maps of urban expansion, hypsometry and hydrography were also created. By analyzing the maps, it was possible to identify the main changes that occurred in the region over a period of 36 years. Land cover analysis revealed a pattern of constant urban growth, accompanied by a decrease and, in some cases, regeneration of vegetation cover. Substantial changes were also noted in local agriculture, due to the presence of soybeans, which gained space from the 2000s onwards. The hypsometry and hydrography maps indicate that the territorial expansion of Apucarana occurred towards the drainage headwaters, configuring an urban space with the presence of several watercourses. The other part of the analysis it was conducted by six sample sections, where on-site visits were conducted. Section 1, Parque da Raposa indicated silting and the presence of an energy sink requiring constant maintenance. Section 2 of Lake Schmidt presented several problems, such as a deteriorating dam, pollution, and irregular construction in APP. Section 3, Ribeirão Biguaçu region highlighted that revitalization does not encompass all the definitions of environmental laws. Section 4 of Praça dos 70 anos presents plumbing and frequent challenges. Section 5 of Jaboti Park indicated the presence of urbanization near the lake. And section 6, the region at the source of the Pirapó River, due to its location, is subject to pollution and degradation of water quality. The visits helped to identify the problems caused in water bodies by urban pressure, such as canalization of water courses, pollution of springs, soil sealing and occupation of permanent preservation areas. Analyzing the impacts of urbanization on bodies of water is extremely important to establish a balance between urban growth and environmental preservation, aiming to guarantee a sustainable future for cities and the environment.